Hazardous waste management - LaGrega, Michael D. (McGraw-Hill, 2001)
The last two decades have seen the emergence of a versatile and powerful method of computational engineering mechanics, namely the boundary element method. This book, which incorporates the massive development of the BEM technology that has occurred in the last decade, describes the formulation of boundary element methods for almost all applications of the method. For ease of use, a simple utilitarian and tutorial approach is adopted in the initial chapters, introducing the basic background needed to learn the method. Simple but detailed instructions for its application to heat transfer and stress analyses are then dealt with, before moving on to more complex formulations in the later chapters. Fully supported by numerous case studies, this is a comprehensive guide to the subject.